2022
DOI: 10.2478/sg-2022-0007
|View full text |Cite
|
Sign up to set email alerts
|

Origin and genetic nature of polyploidy in paleoendemic coast redwood (Sequoia sempervirens(D. Don) Endl.)

Abstract: It is not known when the polyploid coast redwood (Sequoia sempervirens) evolved from its diploid ancestors, and what is its type of polyploidy. Whether close relatives of Sequoia, giant sequoia (Sequoiadendron giganteum) and dawn redwood (Metasequoia glyptostroboides), have possibly contributed to the ancestry of hexaploid of Sequoia remains an open question. The nature of hexaploidy in Sequoia has baffled biologists for more than a century. Based on the chromosome configurations in Sequoia, G. Ledyard Stebbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…In addition to this hypothesis, our analysis suggests that dramatic genome reorganization during diploidization may result in the accumulation of deleterious mutations, and only a limited number of gymnosperm species can survive the genome shock. As reported previously, chromosomes in S. sempervirens meiotic cells are mostly in a bivalent state, but a few are in a multivalent state ( Ahuja and Neale, 2002 ). It has been proposed that S. sempervirens may be a complex species with different types of hexaploids and distinct genotypes ( Ahuja and Neale, 2002 ).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…In addition to this hypothesis, our analysis suggests that dramatic genome reorganization during diploidization may result in the accumulation of deleterious mutations, and only a limited number of gymnosperm species can survive the genome shock. As reported previously, chromosomes in S. sempervirens meiotic cells are mostly in a bivalent state, but a few are in a multivalent state ( Ahuja and Neale, 2002 ). It has been proposed that S. sempervirens may be a complex species with different types of hexaploids and distinct genotypes ( Ahuja and Neale, 2002 ).…”
Section: Discussionsupporting
confidence: 72%
“…Our phylogenetic analyses of single-copy genes using three independent software programs (QuIBL, MSCquartets, and PhyloNet) also indicated that ILS rather than hybridization led to the inconsistent phylogenies ( Figure 3 ). The three extant redwood species exhibit both conserved and variant morphological and embryological characters ( Ahuja and Neale, 2002 ). The lineage-specific mutations and morphologies could have been caused by the independent evolutionary trajectories of the three species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations